The Politics of Law Enforcement of Corruption in Indonesia in the Criminal Justice System - Saraswati, Ni Nyoman Putri Buana Ariani; Rafiq, Jihan; Perdana, Andi Rangga; Arifin, Ridwan; Rahayu, Sang Ayu Putu (Faculty of Law, Universitas Negeri Semarang, 2023)
This study critically examines the intricate nexus between law enforcement and political influences in the context of anti-corruption efforts within Indonesia's criminal justice system. The research navigates the multifaceted landscape of how corruption cases are handled, investigated, and prosecuted, aiming to unravel the subtle dynamics that shape outcomes. Beyond a mere exploration of statutory frameworks, the study delves into the complex interplay between legal processes and political considerations, shedding light on the political dimensions embedded in the enforcement of anti-corruption measures. In Indonesia, where corruption has been a persistent societal challenge, understanding the politics of law enforcement is paramount. The analysis encompasses the roles played by diverse actors, including law enforcement agencies, the judiciary, and political entities. The research adopts a multidisciplinary approach, integrating legal analysis and insights from political science to provide a holistic understanding of the complexities involved. Beyond a descriptive account of legal provisions, the study investigates how political considerations may impact the prioritization, investigation, and prosecution of corruption cases. The findings of this research hold significance for policymakers, legal practitioners, and scholars alike, offering insights that may inform potential reforms and strategies to strengthen the nation's resolve in combatting corruption. By fostering a nuanced understanding of the politics entwined with law enforcement, the study contributes to broader conversations on achieving transparency, accountability, and justice within Indonesia's anti-corruption framework.